Fluorescent Sensors of Phosphate Containing Biomolecules. Issue 3 (9th December 2020) - Nag, Arundhati; Das, Samir
Abstract: Phosphates are an essential functional group in living organisms. Phosphates are required to synthesize ATP, the energy unit in cells, and the synthesis of DNA and RNA, phosphoproteins, phospholipids, and various metabolites. This article is focused on reviewing current research on fluorescent sensing of biologically relevant phosphate functionalities in an aqueous environment or more complex environments such as live cells. There are three different approaches for the fluorescent detection of phosphates. These involve using metal‐ligand complexes as sensors, using metal‐free small molecules as sensors, and using protein or peptide molecules as sensors. The utilization of these approaches for fluorescent sensing of different phosphate‐containing biomolecule classes such as nucleoside polyphosphates, phosphorylated peptides, phosphorylated proteins, pyrophosphates, phospholipids, and RNA are discussed. Abstract :